Structural, Raman and optical investigations of TiO2 nanoparticles prepared using hexamethylenetetramine. (4th March 2022) - Joslin Ananth, N.; Gowri Shankar Rao, R.; Sherlin Vinita, V.; Samuel, J.; Shabna, S.; Shajin Shinu, P. M.; Suresh, S.; Samson, Y.; Biju, C. S.
Abstract: Pure TiO2 and Cu doped TiO2 nanoparticles were prepared by a simple solution approach using hexamethylenetetramine as a chelating agent. The XRD analysis confirmed that the synthesized sample has a hexagonal wurtzite structure. Further, the average crystallite size of pure TiO2 and Cu doped TiO2 estimated from the Debye-Scherrer formula is found to be 10 nm and 9 nm respectively. In the Raman spectrum, the bands for the range 125–635 cm −1 ascertains the anatase crystal structure, while the shift in the position of the principal peak of the doped sample toward higher wavenumber indicates that the dopant may extend some defects and/or surface oxygen vacancies in the doped sample. From the photoluminescence spectrum polychromatic emissions are observed in the range 340–500 nm. The UV-Vis result showed that the absorption edge for Cu doped TiO2 extended to the visible region when compared to the pure TiO2 nanoparticles. The optical band gap of pure and Cu doped TiO2 nanoparticles is also found to be 3.06 eV and 2.92 eV, respectively. The observed reduced band gap can serve as a potential candidate for the degradation of organic pollutants. GRAPHICAL ABSTRACT: UF0001